Application of BUMDES and MSME Technology through Collaborative Model Village Marketplace Design: Rasch Model Analysis of West Sumbawa Community Perceptions - Hari Asgar; Ahdi Topan Sofyan (Postgraduate, University of Mataram, 2023)
West Sumbawa Regency consists of 8 sub-districts,57 village areas, and seven sub-districts. In the district area, institutionally, 57 Village-Owned Enterprises (BUMDES) have been formed, which are spread across each sub-district. BUMDes is a business entity that is strongly supported by social capital, in addition to financial capital from the Village Revenue and Expenditure Budget (APBDes), which includes all efforts to strengthen the rural economy and is required to be the answer to problems of improvement economy and community welfare in the village. BUMDes is a means of driving the economy through various types of business in accordance with the village's potential. BUMDes in Taliwang District, West Sumbawa Regency, has a Savings and Loans Business Unit (USP), procurement of Office Stationery (ATK), sales of Fuel Oil (BBM), procurement of fertilizers and agricultural medicines, trade in agricultural and marine products, as well as communication services and transportation. The BUMDes in Maluk District, West Sumbawa Regency, have various businesses such as village stalls, market units, building management, boarding houses, and waste levies. Lastly, BUMDes in Seteluk District, West Sumbawa Regency, has economic activities in the form of distribution of necessities, Savings and Loan Business Units (USP), food crop production, plantations, animal husbandry, and fisheries, as well as mining, special energy, and management of minerals C. Apart from that, BUMDes in Seteluk District, West Sumbawa Regency, has several superior products or commodities such as freshwater fish, livestock, and Trigona honey